2019
DOI: 10.1002/mgg3.999
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ‐CMPK1 contributes to cell proliferation of non‐small cell lung cancer by elevating cyclin D1 via sponging miR‐302e

Abstract: Background: It is well recognized that competing endogenous RNA (ceRNA) regulatory network is linked to the development and progression of cancer, including non-small cell lung cancer (NSCLC). Herein, we aimed to explore the functional role of circ-CMPK1/miR-302e/cyclin D1 ceRNA signaling in NSCLC. Methods: GEO database (GSE10 2287) was utilized to screen differentially expressed miRNAs in NSCLC. Quantitative reverse transcription PCR (qRT-PCR) and western blotting assays were used to determine gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…A recent study shows that circ-CMPK1 promotes NSCLC cancer cell proliferation through increasing cyclin D1 expression by acting as a sponge of miR-302e. 20 Another study reports that circ- a newly discovered circRNA in 2018, we did not find more studies about the role of hsa_circ_0007385 in NSCLC or in other disease. 14 In addition, the molecular mechanisms about the regulatory role of hsa_circ_0007385 in NSCLC were not investigated in this study, which was due to that there has been a previous study illustrating the effect of hsa_circ_0007385 on NSCLC cell functions, and the major aim of this study was to assess the clinical value of hsa_circ_0007385 in NSCLC.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A recent study shows that circ-CMPK1 promotes NSCLC cancer cell proliferation through increasing cyclin D1 expression by acting as a sponge of miR-302e. 20 Another study reports that circ- a newly discovered circRNA in 2018, we did not find more studies about the role of hsa_circ_0007385 in NSCLC or in other disease. 14 In addition, the molecular mechanisms about the regulatory role of hsa_circ_0007385 in NSCLC were not investigated in this study, which was due to that there has been a previous study illustrating the effect of hsa_circ_0007385 on NSCLC cell functions, and the major aim of this study was to assess the clinical value of hsa_circ_0007385 in NSCLC.…”
Section: Discussionmentioning
confidence: 69%
“…In the last two decades, there have been more and more mode‐of‐action studies revealing the functions of circRNAs in NSCLC. A recent study shows that circ‐CMPK1 promotes NSCLC cancer cell proliferation through increasing cyclin D1 expression by acting as a sponge of miR‐302e 20 . Another study reports that circ‐FGFR1 overexpression enhances migration, invasion, proliferation and immune evasion in vitro as well as promotes resistance to anti‐PD‐1 treatment in vivo in NSCLC 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al alleged that circ_100290 improved cell growth and glycolysis of oral squamous cell carcinoma by acting as a ceRNA for miR-378a to relieve the inhibition of GLUT1 [34]. And the circ-CMPK1/ miR-302e/cyclin D1 axis was disclosed in NSCLC [35]. Herein, circ_0000284 was shown to counteract the miR-377-3p-mediated PD-L1 suppression, consequently increasing the expression of PD-L1, which further caused the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated circRNAs have been manifested to be closely related to the proliferation and metastasis of non-small cell lung cancer (NSCLC) cells and have the potential to be diagnostic biomarkers of lung cancer [ 4 , 5 ]. For instance, circCMPK1 (hsa_circ_0012384) positively modulated cell proliferation of NSCLC cells by increasing cyclin D1 expression by sponging miR-302e [ 6 ]. Li et al reported that circ_0000003 could accelerate the progression of NSCLC by promoting the proliferation and metastasis via the miR-338-3p/IRS2 pathway [ 7 ].…”
Section: Introductionmentioning
confidence: 99%